Pengaruh Tingkat Kemasakan terhadap Kuantitas Hasil dan Daya Simpan Benih Padi (Oryza sativa L.) Varietas Inpari Sidenuk di PP Kerja - Nur Fitrianingsih (Vegetalika, 2018)
Rice demand will continuously increase along with population growth rate. At now needs of rice seed in Central Java can not be fulfill it. The majority of rice seed in Indonesia is supplied by seed producers or seed company. PP Kerja is one of private rice seed producer who contribute to fulfill rice seed demand in Central Java. To increase rice seed productivity, research on rice harvesting at various stages of maturity to produce maximum quantity and yield quality in PP Kerja is important. Rice harvest at physiological maturity will produce maximum growth rate and seed vigour, and also plant growth in the field so that it will increase the yields. This research was done in June 2017 until December 2017 in rice field of PP Kerja, seed technology laboratory, and greenhouse. This experimental design research used was split plot design with the maturity stages as the main plot and the length of storage as the sub plot with 3 blocks as repetition. Maturity stage consists of four stages there were yellow maturity ½ of panicles, yellow maturity ¾ of panicles, full yellow maturity of panicles, and harvest recommendation at now. Storage length consists of four levels there were 0 month, 1 month, 2 month, 3 month. The data were analyzed with variance analysis at 5% of different level followed by HSD test, optimum maturity was determined with regression analysis at 5% of significance level. Results of the research showed that harvesting at full yellow maturity of panicles produces the highest harvest weight and dry storage weight, and also the best storability there are maximum physiological quality such as germination, vigour index, leaf area, plant height, number of leaves, and hypothetical vigour index.